Comportamiento agronómico y valor nutritivo de diez variedades de pastos en diferentes estados de madurez, en la parroquia La Guayas del cantón El Empalme. - Baque Murillo, Hamlethabad Mauricio (2011)
Pastures and fodder are the basis of animal feed and other efficient use of grass could meet much of the nutritional requirements of livestock. In the grounds of the parroquia Ají The Canton Guayas El Empalme was established research "agronomic performance and nutritional value of ten varieties of grasses in different stages of maturity, where aims were to determine the agronomic performance of varieties pastures in three stages of maturity and establish the nutritional value of the ten varieties of grasses. We studied ten varieties of grass (v1: Common Savoy, v2: Savoy Tanzania, v3: Savoy Dwarf, v4: Savoy Tobiata, v5: Andropogus; star v6, v7 Miel decumbens v8, v9 and v10 Brizhanta Mulato, and the factor ( E), three crop ages: (e1: 21, e2, e3 42 and 63). Design We used a randomized complete block (DCA) with ten plants per experimental unit. The highest plant height was reported to Andropogon gayanus to 42 days to 125.20 and Tanzania 63 days to 197.20 cm, weight of forage at 21 and 63 days Andropogon gayanus with 2.43 and 5.05 kg , at 42 days B. mulatto with 11.53 kg weight to leaf Andropogon 21Day and B. mulatto at 42 and 63 days (1.24, 6.53 and 2.53 kg) weight stem at 21 and 63 days Andropogon gayanus (1.19 and 2.94 kg) at 42 days (5, 00 kg), the best leaf: stem Tanzania 21 days, Mulato Tobiata 42 days and 63 days (2.39, 2.77 and 1.25), length of Andropogon gayanus leaves at 21 and 42 days (45.33 and 65.13 cm) and Tobiata 63 days (101.00 cm) wide sheet Tobiata at 21, 42 and 63 days (2.87, 3.20 and 3.74 cm), number of leaves B. mulatto 21, 42 days and B. decumbens 63 days (137.07, 281.27 and 639.40) in the same form occurs on the stalk (46.80, 72.53 and 129.93). The highest protein levels were obtained with the grass common Savoy, Honey, Andropogon brizantha gayanus and 42 days with 15.20, 12.90 and 15.01% protein.